2014
DOI: 10.1093/arclin/acu042
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Repeatable Battery for the Assessment of Neuropsychological Status Effort Scale and Effort Index in a Dementia Sample

Abstract: The aim of the current study was to compare two embedded measures of effort for the repeatable battery for the assessment of neuropsychological status (RBANS). Sensitivity and specificity of the Effort Index (EI) and Effort Scale (ES) were compared in a sample of individuals with genuine memory impairment (MI) and individuals coached to simulate MI. Overall, the EI yielded a sensitivity of 0.89 and specificity of 0.41, while the ES yielded a sensitivity of 0.88 and specificity of 0.81. When those in the MI gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…This profile of impairment is more likely to be seen in AD, which is characterised by a deficit in episodic memory, than in non-AD dementias. Paulson et al (2015) and Dunham et al (2014) investigated the ES in both good and suspect effort groups. They found sensitivity of 0.71 and 0.88 and specificity levels of 0.42 and 0.81 respectively.…”
Section: Test Of Memorymentioning
confidence: 99%
“…This profile of impairment is more likely to be seen in AD, which is characterised by a deficit in episodic memory, than in non-AD dementias. Paulson et al (2015) and Dunham et al (2014) investigated the ES in both good and suspect effort groups. They found sensitivity of 0.71 and 0.88 and specificity levels of 0.42 and 0.81 respectively.…”
Section: Test Of Memorymentioning
confidence: 99%
“…Likewise, after every test session participant had to indicate the effort, concentration and motivation they needed to perform the tests. A 100 mm effort visual analogue scale was used, ranging from "0:little" to "100:much" [21,22].…”
Section: Assessment Of Subjective Ratingsmentioning
confidence: 99%
“…Table 1 shows mean age, sample size, cutoff score, sensitivity, specificity for the respective experimental groups, and PVTs when a 5% base rate of invalid performance is assumed. Aside from a study examining RBANS embedded PVTs, which included a simulator group with a mean age of 27.8 (Dunham et al, 2014), the mean age for all groups included in the studies was greater than 64 years. Across measures, sensitivities ranged from 60% to 100% and specificities ranged from 28% to 100%.…”
Section: Resultsmentioning
confidence: 99%
“…Studies that reported only specificities, and not also sensitivities, were excluded since sensitivity data were required for Bayesian analyses. Measures for which specificity and sensitivity data were reported include: Test of Memory Malingering (TOMM; Bortnik et al, 2013), Rey 15-item test (Bortnik et al, 2013), MSVT (Singhal et al, 2009), Nonverbal MSVT (NV-MSVT; Singhal et al, 2009), the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) Effort Index (EI; Bortnik et al, 2013; Dunham et al, 2014; Paulson et al, 2015), and RBANS Effort Scale (ES; Dunham et al, 2014; Paulson et al, 2015). Peer-reviewed publications included in the McGuire et al (2019) review were examined to confirm sample sizes, cut scores, and classification accuracy statistics.…”
Section: Methodsmentioning
confidence: 99%